ANALYSIS OF FORMULATION MEDIA FOR PLANTING OYSTER MUSHROOM (Pleurotus ostreatus)AGRICULTURAL WASTE BASED MATERIALS - Siti Mardiana; Ellen Lumisar Panggabean; Indah Apriliya; Muhammad Usman (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
The effort of Indonesian people to fulfill their protein intake in an economically accessible way is by producing and consuming oyster mushrooms, because their protein content was viable as an alternative to animal-based products. Combination of sugarcane bagasse, palm fronds (PKS), and sawdust can be used as growing medium for oyster mushrooms. The aim of this study was: (1) to analyze the change in the pH of the combination media formulation of Palm Oil Frond Waste (PKS), sugarcane bagasse, and sawdust; (2) identifying the composition of nutrients in the aforementioned agricultural waste as a growing medium for oyster mushroom. This study was composed of two steps: 1) Preparing the composition of the growing medium from agricultural waste; and 2) Analyzing nutrient composition of the growing medium of oyster mushroom. The research was conducted by using Analysis of Variance (ANOVA) with a Non-Factorial Completely Randomized Design (RAL). The combination of oyster mushroom growing medium from palm fronds, sugarcane bagasse, and sawdust has different pH levels and nutritional contents. The combination of M0 – M8 oyster mushroom growing medium has the suitable level of pH to grow the mushrooms at 6,5 – 8,0 pH. From the formulation analysis of nutrient in the combination of M0 – M8, it can be used as a reference for the nutrient content of oyster mushrooms growing medium from palm fronds and sugarcane bagasse.